Influencer Liability for the Dissemination of Online Gambling Through Electronic Systems - Rizky Ardhya Garini; Hanuring Ayu Ardhani; Hafiz Zakariya (Jurnal Ilmu Hukum Kyadiren, 2026)
The rapid growth of social media has significantly expanded the dissemination of online gambling promotions through electronic systems, with influencers playing an increasingly prominent role. This development raises important questions regarding the adequacy of Indonesia’s legal framework and the scope of criminal liability applicable to influencers engaged in such promotional activities. This study examines the adequacy of Indonesia’s legal regulations governing the promotion of online gambling through electronic systems and develops a framework for influencer liability based on H.L.A. Hart’s (1968) theory of criminal responsibility. Employing a normative legal research method, the study adopts statutory, conceptual, and case approaches through the analysis of legislation, judicial decisions, and legal doctrine. The findings indicate that the harmonization between the Indonesian Criminal Code and Law Number 1 of 2024 on Electronic Information and Transactions provides a sufficient legal foundation for addressing online gambling promotion. However, the existing regulatory framework does not explicitly govern promotional activities conducted by influencers in digital environments. To address this gap, the study proposes a framework of criminal liability based on four essential elements: a valid legal basis, the existence of culpability, criminal responsibility, and the absence of grounds for exculpation. This framework enhances legal certainty while strengthening the effectiveness of criminal law enforcement against the dissemination of online gambling promotions through electronic systems in Indonesia.